2001
DOI: 10.1021/ma0017135
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Polymerization of Ethylene in Emulsion

Abstract: Ethylene polymerization catalyzed by nickel(II) keto-ylide complexes has been performed in water to yield a latex of linear PE. Colloidal stability is highly enhanced by the use of a miniemulsion technique to disperse the catalyst prior contact with the monomer. Latex of typically 200 nm particle diameters and up to 10% solids are generated by this method. The influence of several factors (temperature, pressure, solids) onto the polymerization is studied in detail. The surfactant adsorption isotherms onto thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 36 publications
0
85
0
7
Order By: Relevance
“…2 Recently, it was demonstrated that ethylene can be polymerized in aqueous systems in a catalytic fashion by Ni(II) complexes. [3][4][5][6] By virtue of this novel synthesis, long chains of polyethylene can be generated in a well-controlled environment and at ambient temperature. Thus, it could be shown that aqueous PE dispersions can be produced.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, it was demonstrated that ethylene can be polymerized in aqueous systems in a catalytic fashion by Ni(II) complexes. [3][4][5][6] By virtue of this novel synthesis, long chains of polyethylene can be generated in a well-controlled environment and at ambient temperature. Thus, it could be shown that aqueous PE dispersions can be produced.…”
Section: Introductionmentioning
confidence: 99%
“…The average particle sizes of the dispersions obtained by this procedure are typically in the range from 100 to 500 nm. [45][46][47][48][49]63 The preparation of dispersions with solids contents of up to 30 % has been reported. 46,47 Catalyst activities of up to 1.7×10 5 TO h -1 have been published to date for the preparation of polyethylene dispersions.…”
Section: Polyolefin Dispersionsmentioning
confidence: 99%
“…[30,31] Regarding polymer particle formation in the ethylene polymerization with a catalyst miniemulsion, it can be assumed that in the case of semicrystalline polymer the latter precipitates in the miniemulsion droplets rapidly, forming new particles. Average particle sizes in the range of 70 nm to 1 mm have been reported, [12][13][14][15][16] as determined by light scattering (note, however, that the particles of linear polyethylene are not spherical as observerd by TEM and AFM [32] ). For the case of low-crystalline (and in the example studied also low molecular-weight) ethylene-1-olefin copolymers, which have a much higher miscibility with the organic phase present in the miniemulsion droplets (in this case 1-olefin copolymer and some aromatic solvent), Claverie et al have shown that the number of polymer particles obtained is equal to the number of miniemulsion droplets initially present.…”
Section: Polymerization With Catalyst Miniemulsionsmentioning
confidence: 99%
“…[13] Crystallinity can be reduced by copolymerization, albeit at a further expense of molecular weight and also reduced catalyst activities by comparison to ethylene homopolymerization. [14,15] Polymerization with well-defined complexes as a catalyst precursor as well as with in situ prepared catalysts has been studied.…”
mentioning
confidence: 99%